Empowering parents through early kangaroo mother care a holistic approach to neonatal health: A systematic review - Endah Dessirya; Kusnul Hasanah; Yeni Rustina; Happy Hayati; Mega Hasanul Huda (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The transition of premature infants from the intrauterine to the extrauterine environment is a complex and challenging adaptation process for infants and their mother. Empowering parents through education and support is crucial in navigating these challenges. Propose: To review parental empowerment through early kangaroo care a holistic approach to neonatal health. Method: Systematic review research according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. This literature research uses seven electronic databases, namely PubMed, Proquest, Sciencedirect, Wiley Online, Emerald insight, Sage Journals, and JSTOR. The data search began on September 30, 2024, using the keywords "parent" or "mother" or "maternal" and "infant" or "preterm" and "early" or "immediately" and "skin-to-skin" or "kangaroo-mother-care". The literature criteria used were full texts that discussed prematurity (newborns with a gestational age of <37 weeks), mothers who performed early KMC, parents who performed early KMC, the outcomes measured in this study were infant outcomes (morbidity, mortality, physiological status, weight, and length of stay) and maternal outcomes (exclusive breastfeeding, maternal mental health), and this study used a randomized control design. This study is registered with PROSPERO (CRD42025633170). Results: The search process identified 318 articles. Further screening resulted in a final sample of 7 articles. The review results showed that early KMC has benefits for both mothers and infants. Benefits of early KMC for mothers include increased exclusive breastfeeding, reduced depression, and increased maternal self-satisfaction in caring for preterm infants. Furthermore, in preterm infants, early KMC has been shown to improve physiological stability, weight gain, reduce mortality, morbidity, infections, weight gain, and reduce length of hospitalization. Conclusion: Early implementation of KMC not only provides clinical benefits for preterm infants, but also contributes to improved maternal mental health. These findings support the promotion of KMC as a standard intervention in neonatal intensive care units to optimize short- and long-term outcomes for mothers and preterm infants.